“The Magnificent Seven” Technology Stocks and Their Impact on the S&P 500: A Review 4 Years Later - Dimiter Nenkov Nenkov (Finance, Accounting and Business Analysis)
Purpose: The subject of this research is the performance of the S&P 500 and the influence of the large technology stocks on it. The interest to this issue is provoked by the continued record-breaking process in the levels of the US stock market. The purpose of the study is to find out: whether recent growth of the index and of the seven large companies (Apple, Amazon, Microsoft, Alphabet, Meta Platforms, Nvidia и Tesla) is supported or not by the key financial indicators, and to what extent the index indicators are influenced by the seven large technology stocks.